The Short-Term Effect of Whey Compared with Pea Protein on Appetite, Food Intake, and Energy Expenditure in Young and Older Men. Issue 2 (22nd January 2020) - Hawley, Aubree L; Gbur, Edward; Tacinelli, Angela M; Walker, Sam; Murphy, Allie; Burgess, Regan; Baum, Jamie I
ABSTRACT: Background: Diets higher in protein have been reported to improve age-related changes in body composition via increased energy expenditure, shifts in substrate oxidation (SO), and decreased appetite. However, how protein source (e.g., animal compared with plant protein) affects energy expenditure, appetite, and food intake as we age is unknown. Objectives: The objective of this study was to evaluate the effect of protein source as part of a high-protein breakfast on appetite, food intake, energy expenditure, and fat oxidation in young men (YM) compared with older men (OM). Methods: This study used a randomized, single-blinded crossover design, with a 1-wk washout period between testing days. Fifteen YM (mean ± SD age: 25.2 ± 2.8 y) and 15 OM (67.7 ± 4.5 y), healthy adults, participated in the study. Participants arrived fasted and consumed an isocaloric, volume-matched, high-protein (40-g) test beverage made with either an animal [whey protein isolate (WPI)] or plant [pea protein isolate (PPI)] protein isolate source. Markers of appetite and energy expenditure were determined at baseline and over 4 h postprandial. Results: There was a significant effect of time, age, and protein source on appetite ( P  < 0.05). There was no effect of protein source on plasma markers of appetite, food intake, energy expenditure, and SO. After controlling for body weight, OM had decreased energy expenditure ( P  < 0.05) and lower fat oxidation ( P  < 0.001) compared with YM. Conclusions: This study indicates that a high-protein breakfast containing WPI or PPI exerts comparable effects on appetite, energy expenditure, and 24-h energy intake in both young and older healthy adult men. This trial was registered at clinicaltrials.gov as NCT03399812.